Elastohydrodynamic lubrication study of hard rolling contact using boundary element method - Onsa, M.H.; Sapuan, Salit Mohd; Basri, S. B.; Megat Ahmad, Megat Mohamad Hamdan; Maleque, Md. Abdul (Emerald Group Publishing Ltd., 2001)
Presents a study on the application of boundary element method (BEM) to the solution of elastohydrodynamic lubricated hard rolling contacts in comparison with a solution using finite difference method (FDM). The developed program for the solution of Reynolds equation and the elasticity equation give results of pressure distribution and the lubricant film thickness for steady state, isothermal Newtonian lubricant behavior. Compares the BEM results and the computer effort with the solution using FDM. Uses an iterative Newton- Raphson method to solve the non-linearity of the problem. Discusses the effects of Hertzian pressure and rolling speeds on film thickness and pressure distribution. The numerical scheme of BEM has proved to have the advantage of being very effective and optimum in terms of accuracy, less computational effort and good constancy compared to other applied numerical techniques.